Reconstructions of Gender and Information Technology Women Doing IT for Themselves - Corneliussen, Hilde G. (Springer Nature, 2024)
This open access book explores what makes women decide to pursue a career in male-dominated fields such as information technology (IT). It reveals how women experience gendered stereotypes but also how they bypass, negotiate, and challenge such stereotypes, reconstructing gender-technology relations in the process. Using the example of Norway to illuminate this challenge in Western countries, the book includes a discussion of the "gender equality paradox", where gender equality exists in parallel with gender segregation in fields such as IT. The discussion illustrates how the norm of gender equality in some cases hinders rather than promotes efforts to increase women's participation in technology-related roles.